Disulfiram Induced Psychosis: A Case Report - D. R. Survilaitė; R. Žemaitytė (Neurologijos seminarai)
Introduction. Disulfiram is one of three medications approved by the Federal Drug Administration (FDA) to treat alcohol dependence. Patients tend to abstain from alcohol to avoid the unpleasant effects of alcohol toxicity. There may be some side effects, the most common of which are drowsiness, unusual tiredness, headache, metallic taste in mouth, skin rashes, decreased libido. Disulfiram induced psychosis is a psychiatric side effect that occurs very rarely.